Atlas of Staging in Gynecological Cancer - Smith, J. Richard; Healy, Jeremiah; Del Priore, Giuseppe (Springer London : Imprint: Springer, 2008)
Atlas of Staging in Gynecological Cancer gives a practical approach to the topic and is designed to be used in conjunction with diagnostic procedures between the surgeon and the radiologist. This book describes the two common staging regimes used by all units across the world, namely, the FIGO and TNM systems. The landscape format allows each chapter to open on the left hand side and read across the double page, enabling the reader to see FIGO and AJCC staging together at the same time. Each chapter also has a separate section on Epidemiology, Diagnosis, Management, and a Summary section highlighting key points. The content of Atlas of Staging in Gynecological Cancer takes the reader through each gynecological cancer with a short text accompanying clear radiographic images with explanatory legends. Staging is also shown in pictorial form to aid clarity, with many tables further explaining suggested approach and workflow. The book will be of particular interest to the multi-disciplinary team that looks after this group of patients namely, clinical and radiation oncologists, surgeons, pathologists, radiologists and specialist nurses, all with their respective trainees.